Development and evaluation of polymerase chain reaction assay to detect Burkholderia genus and to differentiate the species in clinical specimens - Cheah, S.H.; Suppiah, J.; Thimma, J.S.; Vadivelu, J. (Blackwell Publishing Ltd., 2010)
Molecular-based techniques are becoming desirable as tools for identification of infectious diseases. Amongst the Burkholderia spp., there is a need to differentiate Burkholderia pseudomallei from Burkholderia cepacia, as misidentification could lead to false treatment of patients. In this study, conventional PCR assay targeting three genes was developed. Primers were designed for the amplification of Burkholderia genus-specific groEL gene, B. pseudomallei-specific mprA gene and B. cepacia-specific zmpA gene. The specificity and sensitivity of the assay was tested with 15 negative control strains and 71 Burkholderia spp. isolates including positive controls B. pseudomallei K96243 and ATCC B. cepacia strain. All B. pseudomallei strains were positive for groEL (139 bp) and mprA (162 bp), indicating a sensitivity of 100%. All B. cepacia strains produced amplicons for detection of groEL and zmpA (147 bp). Specificity using negative strains was 100%. In this study, a PCR assay specific for the detection of Burkholderia spp. and differentiation of the genus B. pseudomallei and B. cepacia was developed. The conventional assay has to be performed separately for each species due to the similar size of the PCR products amplified. This format may therefore be recommended for use as a diagnostic tool in laboratories where real-time PCR machines are not available. However, the real-time PCR was able to detect and differentiate the genus and species in single duplex assay.